KABUPATEN CILACAP MENUJU SMARTCITY: PENERIMAAN GEN Z-MILLENIAL DALAM VISI CILACAP SMART REGENCY - Alfarizi, Muhammad; Arifian, Rafialdo (Jurnal Inovasi Daerah, 2023)
The development of Cilacap Smart City must consider the needs of its population, even though generally, districts and cities adopt similar Smart City systems. Cilacap is striving to develop Cilacap Smart City with a focus on achieving a balance between urban and rural areas. However, there has been no research on how rural communities, deeply rooted in cultural traditions and local wisdom, respond to this concept. This study aims to uncover the acceptance of the millennial and Gen Z generations in Cilacap towards Smart City, particularly the Cilacap Smart Regency program. In this research, the "Cilacap Smart Regency Millennial-Gen Z Adoption" model based on UTAUT2 theory is employed. The research methodology utilizes an online survey with 163 millennial and Gen Z respondents from Cilacap. Data is analyzed using PLS-SEM techniques and validated for reliability. The research findings indicate that perceptions of security and privacy influence trust in technology, although this trust does not affect the intention to use technology. Self-efficacy and effort expectations influence the intention to use Smart City technology. Trust in the government impacts the perceived value of technology, which in turn affects the intention to use Smart City technology. This study underscores the importance of involving the millennial and Gen Z generations in the development of Cilacap Smart Regency. Other critical factors include robust infrastructure, sustainability, sector collaboration, privacy protection, education, startup support, inclusivity, as well as community evaluation and feedback efforts to achieve success in the Smart City initiative in Cilacap Regency.